Intelligent Decision-making Models for Production and Retail Operations - Guo, Zhaoxia; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book provides an overview of intelligent decision-making techniques and discusses their application in production and retail operations. Manufacturing and retail enterprises have stringent standards for using advanced and reliable techniques to improve decision-making processes, since these processes have significant effects on the performance of relevant operations and the entire supply chain. In recent years, researchers have been increasingly focusing attention on using intelligent techniques to solve various decision-making problems. The opening chapters provide an introduction to several commonly used intelligent techniques, such as genetic algorithm, harmony search, neural network and extreme learning machine. The book then explores the use of these techniques for handling various production and retail decision-making problems, such as production planning and scheduling, assembly line balancing, and sales forecasting.
From the Contents: Introduction -- Fundamentals of intelligent decision-making techniques -- An intelligent decision-making framework for production planning and control -- An intelligent optimization model for order scheduling at factory level.
Keywords: Industrial engineering; Production engineering; Operations research; Management science; Computational intelligence; Industrial and Production Engineering; Operations Research and Decision Theory; Operations Research, Management Science; Computational Intelligence